2014
DOI: 10.1017/s002531541400188x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the population status of the sea urchinDiadema antillarumin northern Puerto Rico

Abstract: The mass mortality suffered by the sea urchin Diadema antillarum between 1983-1984 is considered one of the major causes of coral reef degradation in the Caribbean. Its near disappearance resulted in a disproportionate growth of macroalgae that has led to a 'phase shift' from coral-to-algal dominated reefs. The close relationship between this echinoid and the functioning of coral reef ecosystems makes it imperative to better understand the potential for recovery of its populations. From 2009 to 2011, we assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…The highest (0.75 m −2 ) densities were observed in back-reef E, which is consistent with previous findings associating higher populations to protected back-reefs (Rodríguez-Barreras et al, 2014). Diadema antillarum experienced widespread regional collapse over three decades ago and in recent years have shown moderate recovery (Ruiz-Ramos, Hernández-Delgado & Schizas, 2011;Lessios, 2016), partially due to limited successful recruitment (Mercado-Molina et al, 2015). Flamenco's reefs are not an exception in this trend, as D. antillarum does play a significant role in determining benthic community structure across increasing shoreline distances, but with overall low densities (<1 individual m −2 ), below their capacity sustain critical herbivory functions (Hughes, Reed & Boyle, 1987).…”
Section: Discussionsupporting
confidence: 91%
“…The highest (0.75 m −2 ) densities were observed in back-reef E, which is consistent with previous findings associating higher populations to protected back-reefs (Rodríguez-Barreras et al, 2014). Diadema antillarum experienced widespread regional collapse over three decades ago and in recent years have shown moderate recovery (Ruiz-Ramos, Hernández-Delgado & Schizas, 2011;Lessios, 2016), partially due to limited successful recruitment (Mercado-Molina et al, 2015). Flamenco's reefs are not an exception in this trend, as D. antillarum does play a significant role in determining benthic community structure across increasing shoreline distances, but with overall low densities (<1 individual m −2 ), below their capacity sustain critical herbivory functions (Hughes, Reed & Boyle, 1987).…”
Section: Discussionsupporting
confidence: 91%
“…The highest current densities of D. antillarum have been reported in overfished areas such as Jamaica, and explained in terms of low abundance of predators (Sellers et al 2009;Clemente et al 2010;Idjadi et al 2010). Conversely, densities of D. antillarum have exhibited reductions in no-take reserves where fish stocks have recovered (Brown-Saracino et al 2007;Martín-Blanco et al 2010;Mercado-Molina et al 2015). Nevertheless, small labrids (wrasses) are usually excluded and dismissed as potential predators of D. antillarum (see Harborne et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, other studies reported that increased densities of D. antillarum were associated with decreases in macroalgal density (Maciá, Robinson and Nalevanko, 2007;Myhre and Acevedo-Gutiérrez, 2007) and concomitant increases in juvenile coral abundance (Carpenter and Edmunds, 2006;Edmunds and Carpenter, 2001; Idjadi, Haring, and Precht, 2010). Nevertheless, other reports found no such relationship (Lacey, Fourqurean and Collada-Vides, 2013;Mercado-Molina et al, 2015;Rodríguez-Barreras et al, 2018;Steiner and Williams, 2006).…”
Section: Introductionmentioning
confidence: 93%